Noninvasive neuromodulation techniques for the management of phantom limb pain: a systematic review of randomized controlled trials - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Neuromodulation techniques work by modulating pain perception by inducing changes in polarity of the neuronal membrane and thereby cortical excitability. The aim of this review is to evaluate the efficiency and safety of noninvasive neuromodulation techniques for phantom limb pain (PLP). A systematic literature search in the PubMed, Scopus, Web of Science, and Cochrane Library databases was performed to identify studies investigating the effects of noninvasive neuromodulation for PLP. The included journal articles were assessed with Furlan et al.'s method for examining the risk of bias to assess methodologic quality, and evidence was graded using the GRADE approach. The literature search identified 239 studies. Of these 239, four studies fulfilled the inclusion criteria and were included for data extraction. Two of the studies focused on repetitive transcranial magnetic stimulation (rTMS) whereas two other concentrated on transcranial direct current stimulation (tDCS). The present review showed that there is conflicting evidence to support the use of tDCS in short term and moderate evidence to support the use of rTMS in immediate and short term. It is important to recognize that this evidence comes from a very small sample size. No serious adverse effects were reported. Further information from randomized controlled trials with larger sample size investigating immediate and short-term and long-term effects are needed to clarify the best effective stimulation parameters and number of sessions of tDCS and rTMS for PLP.
Keywords: neuromodulation; phantom limb pain; review; transcranial direct current stimulation; transcranial magnetic stimulation; TRANSCRANIAL MAGNETIC STIMULATION; UPDATED METHOD GUIDELINES; MOTOR CORTEX; FIBROMYALGIA; IMMEDIATE; THERAPY; COMPLEX